Syndrome Nomophobia dengan Komunikasi Interpersonal pada Mahasiswa Tingkat 1 Sarjan Keperawatan di STIKes Karya Husada Kediri - Andika Siswoaribowo (Universitas Muhammadiyah Jember, 2024)
Information and communication technology is continuously developing so that many tools have been created, one of which is a smartphone. With the availability of features on a smartphone, a person can experience nomophobia syndrome, thus affecting social relations with other people, resulting in interpersonal communication problems. The aim of the study was to determine the relationship between nomophobia syndrome and interpersonal communication in first year undergraduate students in nursing at Stikes Karya Husada Kediri. Correlation research design with a cross sectional approach. The sampling technique used total sampling, obtained 92 respondents. The research instrument used a questionnaire. The results of the study showed that most of the nomophobia syndrome was in the moderate category and most of the interpersonal communication was in the moderate category. Data analysis used the Spearman Rank test, the results obtained were p value: 0.001 < : 0.05, so H1 was accepted, meaning that there is a relationship between nomophobia syndrome and interpersonal communication in level 1 undergraduate students in nursing at Stikes Karya Husada Kediri. The correlation value is -0.746, meaning that the strength relationship is included in the strong category, and the relationship between variables is negative, meaning that the lower the incidence of nomophobia syndrome, the better interpersonal communication, and vice versa. Addiction to smartphones causes a person to tend to be more concerned with smartphones than communicating with people around him. It is recommended to always control the use of smartphones so that nomophobia syndrome does not occur and interpersonal communication is maintained.